2019
DOI: 10.1177/0886260519860080
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Family Violence in Childhood, Self-Efficacy, and Posttraumatic Stress Symptoms in Young Adulthood

Abstract: This study aimed to examine the relationship of exposure to family violence (i.e., experiencing parental physical violence [PH] and psychological aggression [PA] and witnessing interparental PH and PA) during childhood and adolescence with posttraumatic stress symptoms (PTSS) during young adulthood. In addition, the mediating role of self-efficacy in this relationship was investigated. Data were collected from a convenience sample of 516 university and college students in Israel (90.7% female and 9.3% male; Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It suggests that family relationships and self-efficacy during the epidemic may both affect the mental health of medical staff. The partial mediating role of self-efficacy in some psychological trait relationships has been supported by relevant research ( Haj-Yahia et al, 2019 ). Indeed, it has been found that self-efficacy was a mediator for the association of daily stress and mental health ( Schönfeld et al, 2019 ).…”
Section: Introductionmentioning
confidence: 87%
“…It suggests that family relationships and self-efficacy during the epidemic may both affect the mental health of medical staff. The partial mediating role of self-efficacy in some psychological trait relationships has been supported by relevant research ( Haj-Yahia et al, 2019 ). Indeed, it has been found that self-efficacy was a mediator for the association of daily stress and mental health ( Schönfeld et al, 2019 ).…”
Section: Introductionmentioning
confidence: 87%
“…This is supported by Hossain, Pearson, McAlpine, Bacchus, Spangaro, Muthuri, Muuo, Franchi, Hess, Bangha and Izugbara (2021) who posit that domestic violence is linked to many poor health outcomes including long-term mental health disorders such as anxiety and depression. Victims of domestic violence can face more challenges such as being unable to go to work (Haj-Yahia et al, 2021). McCloskey (2016) avers that teenagers who are victims of sexual violence are likely to face challenges such as rapid repeat pregnancies during adolescence.…”
Section: The Overview Of Violence In South Africamentioning
confidence: 99%
“…In comparison to men, Arab women have been shown to have lower resilience (e.g., Marciano et al, 2020). Additionally, research has shown that Arab adolescent girls who were exposed to traumatic events are at greater risk of developing internal or external problems, social and interpersonal problems, and difficulties in psychological adjustment (Haj-Yahia et al, 2021). This risk is even higher when one is experiencing several types of This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: The Intersectional Trauma Of Young Arab Women In Israelmentioning
confidence: 99%